A Journal of Three Months$1 (BWalk in Persia in 1884 by Captain John Compton Pyne : s Introduction, Notes and Translation - Afsharian, Marjan; Harris, Russell; Project Muse. (Leiden : Leiden University Press, 2017)
A primary source on a journey to Persia by Captain John Compton Pyne in 1884 revealing the West's fascination with the Middle East in Victorian times. The book includes an introduction by the editors and a transcription of the manuscript with notes and the original illustrations, mainly watercolours. An important historical document and eye-witness account pertaining to Iran, anthropology, area studies, study of 'orientalism' and colonialism, and for historians.
English.
Description based on print version record.
Keywords: Pyne, John Compton -- Travel; Iran; Iran -- Descriptions et voyages; Iran -- Description and travel; Travel; Adventure and adventurers; Adventure and adventurers -- Iran; Personal narratives; History; Electronic books